Implantable self-powered therapeutic pellet for wireless photodynamic/sonodynamic hybrid therapy of cancer recurrence inhibition and tumor regression. (January 2023) - Guan, Hongye; Zou, Pingjin; Lin, Rui; Xiao, Ling; Fang, Zengyi; Chen, Junyang; Lin, Tao; Wang, Yuan; Peng, Yifeng; Zhong, Tianyan; Zhang, Biqin; Lang, Jinyi; et al.
Abstract: Photodynamic therapy (PDT) and sonodynamic therapy (SDT) are prospective cancer therapies that have attracted considerable attention owing to their relative safety. Here, we develop a new implantable self-powered therapeutic pellet that provides wireless PDT/SDT hybrid therapy for low-dose/long-term cancer recurrence inhibition and tumor regression. The miniature pellet contains an integrated self-powered unit, light-emitting diode illuminant, and control circuit. The system is powered by ultrasound energy via the piezoelectric effect. The pellet can deliver therapeutic doses of light into tissues for PDT alongside direct SDT. The wireless PDT/SDT hybrid therapy is shown to be highly efficient in the treatment of breast cancer in mice in vivo (much higher than single PDT or SDT). The system can operate successfully inside the body, and optimized sensitizer activation and wireless control of therapeutic dosimetry mean that it has great potential for cancer treatment. Moreover, it elucidates the critical interplay between existing clinical cancer therapies and future precision therapies. Graphical Abstract: A new implantable self-powered therapeutic pellet that provides wireless PDT/SDT hybrid therapy for low-dose/long-term cancer recurrence inhibition and tumor regression. The miniature pellet contains an integrated self-powered unit, light-emitting diode illuminant, and control circuit. The system is powered by ultrasound energy via the piezoelectric effect. The pellet can deliver therapeutic doses of light into tissues for PDT alongside direct SDT. ga1 Highlights: Wireless PDT/SDT hybrid therapy for low-dose/long-term cancer treatment. Self-powered by ultrasound energy via piezoelectric effect. Delivering therapeutic doses of light into tissues for PDT alongside direct SDT. Highly efficient in the treatment of breast cancer in vivo.